Taxonomy and distribution of holothurians in selected sites within Panabolon Island, Guimaras. - Bachoco, Raian Dennis (2001.)
This study mainly deals with the taxonomy and distribution of sub-tidal holothurians in 2 selected sites based on the predominant substrate and vegetation characteristics, within Panabolon Island. Sampling was done during low tides in the months of March and April 2001., A total of seven species in five genera belonging to families Synaptidae, Holothuriidae and Stichopodidae were recorded from the study area. The family Holothuriidae is the most common (4 species) of the three families. Synapta maculata is the most abundant species (33.33%) followed by Holothuria atra (27.27%) and Holothuria scabra (21.21%). Highest species diversity was observed in the coralline area with strong water movement while densities are highest in areas with seagrass beds.
Thesis (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines in the Visayas, Iloilo City.
Keywords: Holothurians -- Guimaras